Our land, our animals: Herding in Kenya's Kitengela rangelands - International Livestock Research Institute (International Livestock Research Institute, 2012)
Nickson Parmisa, a resident of Kitengela just outside Nairobi in Kenya, talks about the challenges of livestock herding in the face of climate change.